2022
DOI: 10.1038/s41598-022-13600-8
|View full text |Cite
|
Sign up to set email alerts
|

Signature of weak-antilocalization in sputtered topological insulator Bi2Se3 thin films with varying thickness

Abstract: We report a low-temperature magneto transport study of Bi2Se3 thin films of different thicknesses (40, 80 and 160 nm), deposited on sapphire (0001) substrates, using radio frequency magnetron sputtering technique. The high-resolution x-ray diffraction measurements revealed the growth of rhombohedral c-axis {0003n} oriented Bi2Se3 films on sapphire (0001). Vibrational modes of Bi2Se3 thin films were obtained in the low wavenumber region using Raman spectroscopy. The surface roughness of sputtered Bi2Se3 thin fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 37 publications
5
19
0
Order By: Relevance
“…Here, 4F5/2- and 4F7/2-related signals were recorded as distinct peaks at 163.03 and 157.73 eV, respectively, and the shoulder peaks related to the Bi were observed at 161.58 and 156.08 eV. , Figure b reveals the core-level spectrum corresponding to Se 3d. Here, 3d3/2- and 3d5/2-related signals were recorded as distinct peaks at 53.6 and 52.8 eV, respectively. The observed signals are in good agreement with previously reported results for Bi 2 Se 3 thin films, confirming the formation of high-quality crystals in Bi 2 Se 3 thin films synthesized on the PSS.…”
Section: Resultssupporting
confidence: 90%
“…Here, 4F5/2- and 4F7/2-related signals were recorded as distinct peaks at 163.03 and 157.73 eV, respectively, and the shoulder peaks related to the Bi were observed at 161.58 and 156.08 eV. , Figure b reveals the core-level spectrum corresponding to Se 3d. Here, 3d3/2- and 3d5/2-related signals were recorded as distinct peaks at 53.6 and 52.8 eV, respectively. The observed signals are in good agreement with previously reported results for Bi 2 Se 3 thin films, confirming the formation of high-quality crystals in Bi 2 Se 3 thin films synthesized on the PSS.…”
Section: Resultssupporting
confidence: 90%
“…2(b), which is consistent with previous reports. 26,27 The core-level XPS spectra corresponding to Te-3d 5/2 and Te-3d 3/2 are found around 572.4 eV and 582.8 eV with 10.4 eV splitting for our system as exhibited in Fig. 2(c), which is also reliable as reported in previous reports.…”
Section: Xps Analysissupporting
confidence: 91%
“…The XPS signal in Figure 1d,e shows a rich spectrum with Biand Se-related peaks, and a quantitative XPS analysis based on Bi4f and Se3d showed that the stoichiometry of the film reached ∼43%:57%, close to the expected 40%:60% (2 Bi: 3 Se) [52][53][54][55]. According to the previous studies of Bi 2 Se 3 , the peak Se 0 (Figure 1e) indicates elemental selenium (Se) [55][56][57]. Additionally, we performed Raman spectroscopy (Figure 1f,g) at two excitation wavelengths: 532 nm (Figure 1f) and 632.8 nm (Figure 1g).…”
Section: Sample Characterizationmentioning
confidence: 53%